Relational Attachment at Work: A Complementary Fit Perspective on the Role of Relationships in Organizational Life - Ehrhardt, Kyle; Ragins, Belle Rose (Academy of Management Journal, 2019)
Organizational scholars concur that supportive work relationships can attach employees to their workplace and improve the quality of organizational life, but they lack insights into how or why this occurs. Moreover, models of social support focus on what relationships provide without considering the fit between what people need and receive from their work relationships. Addressing these limitations, we developed and tested a theoretical model of relational attachment at work using a complementary fit perspective. After validating measures, we tested, extended, and replicated our model in three field studies. Results revealed that employees became more attached to their organization and experienced more beneficial outcomes when they had stronger psychological attachment to others at work. This relational attachment was not driven by general social support, but, rather, by “relational needs fit,” which reflects employees’ experience of having their needs met by their work relationships. However, receiving more personal support than what was wanted or needed intruded into employees’ privacy boundaries and created a “too close for comfort” reaction whereby they pulled back from their work relationships. This “too much of a good thing” finding indicates that, while positive relationships at work are effective, social support should be tailored to individuals’ needs.